A Proposed Framework For Customs' Transition To Circular Economy - Imam Tri Wahyudi; Indri Riesfandiari; Muhammad Anshar Syamsuddin (WIM Solusi Prima, 2023)
Study on a framework for a customs administration to transitioning to circular economy (CE) is limited. This study aims to propose framework for customs’ transition to circular economy (CE) by modifying high-level framework for green customs with element of policy interventions. The policy intervention is intended to overcome the identified circular economy capabilities gap. By using this modified framework, this study identifies possible policy intervention needed by customs administration to accelerate its transition to CE. The design science research (DSR) approach was followed to develop the framework. Interview were conducted to provide evaluation on the framework; to provide description on current state of circularity in customs business processes; and to provide information needed to identify capabilities gap. This paper suggests several policy interventions, namely: raising the awareness on CE internally and externally; developing roadmap for customs’ transition to CE; enhancing data exchange via national single window; revisiting regulation on bonded recycling zone to attract business. The limitation of policy intervention suggested is regarding its practical implications. Further consultation and discussion with expert on customs and CE is needed to evaluate the feasibility and practicality of the policy interventions proposed.